(untitled) (Faridpur Medical College Journal, 2020)
It is commonly believed that if the first child of a mother is born by normal vaginal delivery, all the subsequent deliveries will follow the same. As a result, such multiparous mothers often neglect routine antenatal check ups and intranatal care which may cause poor delivery outcome. For these reasons, attention should be given to analyze the indication of caesarean section (CS) in women who had history of previous vaginal delivery. Our objective was to know the indications and outcome of CS in multigravid women having a child previously delivered vaginally. This observational cross-sectional study was carried out in the Department of Obstetrics and Gynaecology in Diabetic Association Medical College Hospital, Faridpur. One hundred and ten multigravid women who had undergone elective as well as emergency CS for various indications were included in this study. Most common indication of CS was fetal distress (33.64%). Others were obstructed labour (10.9%), breech presentation (10.9%), and pre-eclampsia (9.09%). In the postpartum period, 75.5% patients were healthy. Others developed sepsis (10.9%) and URTI (8.2%). Most of the babies (95.5%) were alive. Understanding these insights may help both the mother and the caregiver an idea about the associated risks and what actions should be taken for a safe delivery outcome. Faridpur Med. Coll. J. Jul 2019;14(2): 86-89